CONSTRUCTING POSITIVE TRAVEL EXPERIENCE THROUGH LANGUAGE: A DISCOURSE-PRAGMATIC STUDY IN CENTRAL JAVA, INDONESIA - Purnomo, Budi (BASIS (Bahasa dan Sastra Inggris), 2025)
This study investigates how language is used to construct positive travel experiences in online reviews of tour services in Central Java, Indonesia. It aims to reveal the linguistic and pragmatic strategies through which international tourists express satisfaction, gratitude, and interpersonal warmth in digital communication. Drawing upon Discourse Analysis (Fairclough, 1992) and Politeness Theory (Brown & Levinson, 1987), 150 English-language TripAdvisor reviews written by foreign travelers who had participated in tour programs across major destinations in Central Java were analyzed qualitatively through discourse-pragmatic interpretation. The analysis focused on evaluative expressions, politeness markers, and narrative framing that revealed the writers’ affective stance. Findings show that reviewers frequently employed expressive lexical choices, intensifiers, and positive adjectives (e.g., amazing, helpful, friendly) to strengthen affective meaning. Pragmatically, tourists often used direct appreciation, collectivist expressions, and culturally sensitive compliments (e.g., thank you so much, we truly appreciate it) to establish solidarity and warmth. These linguistic strategies demonstrate how reviewers not only evaluate tour services but also enact politeness norms and rapport-building within digital discourse. The study concludes that online reviews extend traditional Indonesian values of sopan santun (courtesy) into digital interaction, reinforcing Central Java’s image as a hospitable and culturally respectful destination in global tourism communication.